A review of the Oriental and Australasian Ptilocera species (Diptera: Stratiomyidae) - Mason, Franco; Rozkošný, Rudolf (Zootaxa, 2011)
The species of Ptilocera Wiedemann, 1820 are re-examined on the basis of extensive historical as well as recent material from several institutions and a critical evaluation of published records. Ten species are distinguished and three of them, P. aureopilosa sp. nov., P. kerteszi sp. nov. and P. simplex sp. nov. are described as new. Ptilocera fastuosa Gerstaecker, 1857, is considered to be a synonym of P. continua Walker, 1851, and P. smaragdifera Walker, 1859 is interperted as a synonym of P. smaragdina Walker, 1849. Lectotypes are designated for P. amethystina Snellen van Vollenhoven, 1857, P. fastuosa, P. quadridentata (Fabricius, 1805) and P. smaragdifera. Seven species (P. amethystina, P. continua, P. kerteszi sp. nov., P. paradisea Lindner, 1951, P. quadridentata, P. simplex sp. nov. and P. smaragdina are mainly confined to the Oriental Region and three to the Australasian Region (P. aureopilosa sp. nov., P. bergi James, 1948, and P. violacea Edwards, 1915). Ptilocera quadridentata was introduced to Japan and Fiji, and P. smaragdina to New Britain. P. bergi is newly recorded from Australia, P. amethystina, P. continua and P. quadridentata from Cambodia, Laos and Vietnam, the first two species also from Myanmar, P. amethystina also from Malaysia and Thailand, and P. continua also from Nepal and Singapore. Diagnostic characters including terminalia of both sexes are illustrated for all species examined and an identification key is compiled.